Thrombin aptasensing with inherently electroactive graphene oxide nanoplatelets as labels - Loo, Adeline Huiling (2013)
Graphene and its associated materials are commonly used as the transducing platform in biosensing. We propose a different approach for the application of graphene in biosensing. Here, we utilized graphene oxide nanoplatelets as the inherently electroactive labels for the aptasensing of thrombin. The basis of detection lies in the ability of graphene oxide to be electrochemically reduced, thereby providing a well-defined reduction wave; one graphene oxide nanoplatelet of dimension 50 × 50 nm can provide a reduction signal by accepting ~22 000 electrons. We demonstrate that by using graphene oxide nanoplatelets as an inherently electroactive label, we can detect thrombin in the concentration range of 3 pM–0.3 μM, with good selectivity of the aptamer towards interferences by bovine serum albumin, immunoglobulin G and avidin. Therefore, the inherently electroactive graphene oxide nanoplatelets are a material which can serve as an electroactive label, in a manner similar to metallic nanoparticles.